2010
DOI: 10.1136/bjo.2010.182774
|View full text |Cite
|
Sign up to set email alerts
|

Causes of cataract surgery malpractice claims in England 1995-2008

Abstract: Aims:To analyse the causes of malpractice claims related specifically to cataract surgery in the National Health Service in England from 1995-2008.Methods: All the malpractice claims related to cataract surgery from 1995-2008 from the National Health Service Litigation Authority were analysed. Claims were classified according to causative problem. Total numbers of claims, total value of damages, mean level damages and paid:closed ratio (a measure of the likelihood of a claim resulting in payment of damages) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 14 publications
(9 reference statements)
1
22
0
2
Order By: Relevance
“…Surgical confusions (ie wrong patient, wrong site or side surgery, wrong procedure or implant) are an infrequent, but important and preventable cause of patient morbidity in general and relevant to ophthalmic surgeons. [2][3][4][5]8,9 The Department of Health in England consultation exercise on 'never events' states that insertion of an incorrect implant is an event that should never happen. 10 Ophthalmologists and orthopaedic surgeons at the Veterans' Health Administration experienced the highest rate of preventable adverse events resulting not only from wrong site procedures, but seemingly high rates of incorrect medical device implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical confusions (ie wrong patient, wrong site or side surgery, wrong procedure or implant) are an infrequent, but important and preventable cause of patient morbidity in general and relevant to ophthalmic surgeons. [2][3][4][5]8,9 The Department of Health in England consultation exercise on 'never events' states that insertion of an incorrect implant is an event that should never happen. 10 Ophthalmologists and orthopaedic surgeons at the Veterans' Health Administration experienced the highest rate of preventable adverse events resulting not only from wrong site procedures, but seemingly high rates of incorrect medical device implantation.…”
Section: Discussionmentioning
confidence: 99%
“…3 Claims relating to biometry errors/ wrong IOL power were frequent in the NHSLA review. 4 The litigation claims in cataract care in the United States are for similar reasons. 5 Following several influential reports on patient safety, learning from clinical failure or incident is now widely regarded as a core principle underpinning improvement in patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate consenting process (combined with poor outcomes) is one of the most common reasons for malpractice litigation in ophthalmology 48. This problem is particularly hard to overcome, as many publications have shown that very little information presented during informed consent is actually retained by the patient 9–13.…”
Section: Introductionmentioning
confidence: 99%
“…Paralelamente, quando observamos as alegações dos autores, somando os que afirmaram perda total e perda parcial da visão, chegamos a um total de 83,5% de descontentamento com a acuidade visual final após intervenção médica. Estes dados parecem indicar que, assim como já observado por outros autores 12,13 , os casos em sua maioria resultam de insatisfação com resultados e não por erro médico.…”
Section: Discussionunclassified